HAEMATOLOGICAL AND BEHAVIOURAL STUDIES OF FRESH WATER FISH, CHANNA ORIENTALIS (SCH) EXPOSED TO NOVEL DERIVATIVE OF 1, 3, 5-TRIAZINE - MANISHA KODAPE,; DIPAK TAYADE,; NANDKISHOR GAWHALE,; DINESH DABHADKAR, (The Bioscan, 2011)
The fish C. orientalis was exposed to triazine derivative i.e.1-phenyl-2-thio (1H)-4-[(1-phenyl-2-thio (1H)-6-amino- 1, 2-dihydro-1, 3, 5-triaz-4-yl)]-amino-6-phenylamino-1, 2-dihydro-1, 3, 5-triazine which was synthesized from 2- phenylimino-4[(2-imino-6-phenylimino)-1, 3, 5-thiadiaz-4-yl]-amino-6-phenylimino-1, 3, 5-thiadiazine. To study the effect of triazine, the experiments were conducted in two different phases. In first phase, lethal concentration of toxicant was determined and in the second phase, toxicity was studied with respect to selected lethal concentration of toxicant. The study revealed that the fishes were sensitive to the triazine derivative, high concentration of triazine was very toxic to aquatic organism. 1, 3, 5-triazine treatment inflicted a drastic reduction in the total count of RBCs and WBCs along with morphological changes in the fish.